Implementation of Curriculum Management and Mulok Kks Learning to Improve Students' Al-Qur'an Reading Standards - Aziz, Rizky Maulana (Khalifah : Jurnal Pendidikan Nusantara, 2023)
The Covid-19 effect is still felt today. One reason for the decline in the quality of religious students is because they cannot read the Qur'an in accordance with the requirements. So that local content of the study of the Scriptures becomes a new discovery. The purpose of this study is to provide an overview of how the management of the Local Content Curriculum Study of the Scriptures (KKS) is implemented in SMP Negeri 2 Salatiga. The use of qualitative research methods, as well as ways of collecting data using observation, interviews, and documentation. Miles and Huberman models are applied to data analysis. In testing the validity of data, using triangulation of sources and techniques. The findings of this research are: 1) The Mulok KKS curriculum planning process requires the making of instructional material and working with various parties, 2) classifying students into different groups for the curriculum, 3) applying the curriculum on Saturdays, and 4) curriculum evaluation, which seeks to be improved.